Influence of Mathematics in The Desertion of Higher Education - Ceballos, Johan; Abalco, Scarlett; González, Daniel; Saltos, Guido; Suquillo, Ximena; Angel, Mauricio (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In the present work the different models of university desertion are analyzed, identifying the factors that have influence in the continuation of the studies of the students. These factors are essentials to defining what will be understood by university desertion and to elaborate the profile of the deserter. In the case of the Universidad de Las Américas (Quito, Ecuador), the main factors that influence the desertion are corroborated with those that have been established according to the existing bibliography and a descriptive study of these data is carried out, in order to elaborate indicators that allow us to predict the behavior of the student population with a higher risk of dropping out. An analysis is made relating the area of Mathematics and the desertion, seeing how this area influences the possibility of a student dropping out.